2009
DOI: 10.1007/s13199-009-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Seed size influences arbuscular mycorrhizal symbiosis across leguminous host-plant species at the seedling stage

Abstract: Eighteen species of the Fabaceae were selected to investigate the relationship between plant seed size and the density of arbuscular mycorrhizal (AM) structures on the roots of young plants. The results demonstrated that seed size showed a strong negative correlation with the density of AM structures: smaller seeds exhibiting higher AM densities, which suggested that seed size may regulate AM symbiosis across leguminous host-plants species in natural habitats. Furthermore, the results also implied that differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
4
3
0
Order By: Relevance
“…Levels of mycorrhizal colonization were similar for all species with the exception of Castilla, which showed no signs of colonization in our experiment, even though the species is known to be facultatively mycorrhizal (Janos 1980). Castilla had much larger seeds (0.5 g) compared to the other four species (0.001-0.03 g), and the presence of larger seed reserves may have delayed establishment of AMF colonization (Allsopp and Stock 1995;Jin et al 2009).…”
Section: Amf Colonizationsupporting
confidence: 46%
“…Levels of mycorrhizal colonization were similar for all species with the exception of Castilla, which showed no signs of colonization in our experiment, even though the species is known to be facultatively mycorrhizal (Janos 1980). Castilla had much larger seeds (0.5 g) compared to the other four species (0.001-0.03 g), and the presence of larger seed reserves may have delayed establishment of AMF colonization (Allsopp and Stock 1995;Jin et al 2009).…”
Section: Amf Colonizationsupporting
confidence: 46%
“…Our results were consistent with the findings of Kitajima (2003) and Jin et al (2009). Seedling growth reductions as a consequence of removal of cotyledons have been reported in soybean (Chin et al, 1977) and Quercus robur L. (Garcia-Cebrian et al, 2003).…”
Section: Effect Of Cotyledon Removal On Growth and Mycorrhizal Dependsupporting
confidence: 93%
“…This could be due to the large seeds of P. pinnata. Jin et al (2009) pointed out that plants with large seeds generally exhibit lower AMF densities. Furthermore, P. pinnata seedlings did not produce fine roots up to 30 days after sowing; it only formed relatively thick roots, which were not colonized by AMF.…”
Section: Colonization Potential Of Amfmentioning
confidence: 99%
“…Our study here showed that AM fungi had a positive effect on E. nutans plant biomass likely via improved uptake of nutrients, water relations, and increasing resistance to pathogens (Newsham et al 1995;Jin et al 2009Jin et al , 2010. Furthermore, AM fungi also increased N and P concentration in shoots and roots of E. nutans.…”
Section: Discussionsupporting
confidence: 53%